Cadmium and Chromium in Selected Canned Goods Commercially Available in the Philippines - Solidum, Judilynn (JPAIR Multidisciplinary Research, 2015)
Heavy metals are both naturally occurring and anthropogenic such that even processed food canned for easy marketing and handling may be contaminated with it. This study aimed to determine the presence or absence of cadmium and chromium in canned fish and meat commercially available in the Philippines. Acid digestion was employed to the solid fish and meat samples prior to quantitative instrumental analysis using Flame Atomic Absorption Spectroscopy (FAAS). The results showed that the canned meat and fish samples tested all contained cadmium and chromium. None of the canned fish and meat samples went beyond the limit for cadmium in food. Canned fish all went beyond the limit for chromium on both California and United States Environmental Protection Agency (EPA) limits. Only CF2 and CF8 went beyond the Center for Food Safety limit in Hong Kong. For canned meat samples, all went beyond the limit set for chromium relative to California EPA standards but not on US EPA and Center for food Safety in Hong Kong limits. All of the levels of cadmium as projected mathematically did not go beyond the acceptable blood levels for both the samples of canned meat and fish. Concentration of chromium from meat when projected in blood did not exceed the safe levels while chromium in CF2 and CF8 exceeded the acceptable blood amounts as mathematically projected.
Keywords: Environmental Toxicology; cadmium; chromium; canned goods; FAAS; Philippines